Efficacy and Safety of Multiple Dosages of Fostamatinib in Adult Patients With Rheumatoid Arthritis: A Systematic Review and Meta-Analysis - Kang, Yaqi; Jiang, Xinrui; Qin, Dalian; Wang, Long; Yang, Jing; Wu, Anguo; Huang, Feihong; Ye, Yun; Wu, Jianming (Frontiers in Pharmacology, 2019)
Background: Rheumatoid arthritis is a type of systemic and complex autoimmune disease characterized by chronic joint inflammation. Spleen tyrosine kinase (Syk) inhibitors are regarded as an effective alternative to existing drugs for the treatment of this disease. However, studies evaluating fostamatinib, a new Syk inhibitor, are either invalid or insufficient. Through a systematic review and meta-analysis, we evaluated the efficacy and safety of fostamatinib at different dosages in rheumatoid arthritis patients that display an inadequate response to methotrexate or disease-modifying antirheumatic drugs. Methods: Randomized controlled trials published between January 2000 and November 2018 were retrieved from PubMed, Embase, Medline, Web of Science, and The Cochrane Library. We also searched a relevant website (www.clinicaltrials.gov) for retrieval of unpublished data. These studies compared different dosages of fostamatinib to placebo, including the intake of 100 mg fostamatinib twice per day (bid) for 4 weeks followed by 150 mg once per day (qd) vs. the intake of 100 mg bid. Results: Two investigators analyzed 11 randomized placebo-controlled trials consisting of 4,218 patients. Compared to placebo, fostamatinib resulted in an obvious reduction in the American College of Rheumatology 20% response standard (weighted mean difference (WMD) 1.96, 95% confidence interval (CI) [1.46, 2.61], P < 0.001) and disease activity score < 2.6 (WMD 4.70, 95% CI [3.14, 7.03], P < 0.001). Regarding safety, the incidence of serious adverse reactions was higher in the fostamatinib group than in the placebo group (risk ratio (RR) 2.10, 95% CI [1.57, 2.80], P < 0.001). The same was true for other adverse events (RR 1.63, 95%CI [1.33, 2.01], P < 0.001). Conclusions: Fostamatinib is an effective and safe therapeutic medicine administered to patients with rheumatoid arthritis over 24 weeks. It can alleviate the degree of swelling and inflammation of the joints. Furthermore, 100 mg bid can be considered the most beneficial regimen over a 24-week period. More data are however needed to clarify the incidence of other adverse events and serious adverse reactions.